2015
DOI: 10.12962/j25983806.v15.i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Warna Dan TSS Limbah Cair Tenun Sarung Samarinda Menggunakan Kitosan Dari Limbah Cangkang Kepiting

Abstract: AbstrakIndustri rumah tangga pembuatan sarung tenun Samarinda menghasilkan limbah cair dengan konsentrasi TSS dan warna yang melebihi baku mutu sehingga memerlukan pengolahan sebelum dibuang ke badan air. Salah satu unit pengolahan yang dapat digunakan adalah unit koagulasi flokulasi dengan menambahkan koagulan. Jenis koagulan yang dapat digunakan salah satunya adalah koagulan dari bahan alam yaitu berasal dari kitosan limbah cangkang kepiting. Tahapan penelitian ini dimulai dengan mempersiapkan koagulan dari … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
2
Order By: Relevance
“…The degree of deacetylation can be calculated using the baseline method from the analysis of chitosan using an FTIR spectrophotometer. Chitosan typically has a degree of deacetylation of less than 70% (Aulia & Rahayu, 2015). In this study, the degree of deacetylation of chitosan was found to be 87% (Table 2), indicating that the obtained sample is indeed chitosan.…”
Section: The Synthesis Of Chitosan From L Vannamei Shellssupporting
confidence: 49%
See 2 more Smart Citations
“…The degree of deacetylation can be calculated using the baseline method from the analysis of chitosan using an FTIR spectrophotometer. Chitosan typically has a degree of deacetylation of less than 70% (Aulia & Rahayu, 2015). In this study, the degree of deacetylation of chitosan was found to be 87% (Table 2), indicating that the obtained sample is indeed chitosan.…”
Section: The Synthesis Of Chitosan From L Vannamei Shellssupporting
confidence: 49%
“…The degree of deacetylation is a parameter used to determine the quality of chitosan by showing the percentage of acetyl groups that can be removed from the chitin yield to become chitosan. The difference between chitin and chitosan lies in the ratio of amino groups (NH2) to acetyl groups (NHCOCH3), which is referred to as the degree of deacetylation (Aulia & Rahayu, 2015).…”
Section: The Synthesis Of Chitosan From L Vannamei Shellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam proses pencelupan warna, digunakan alkali untuk proses fixsasi warna, sehingga pH air menjadi tinggi. Warna limbah sarung tenun cenderung pekat, hal ini dikarenakan tidak semua zat kimia pewarna digunakan dapat berdiksasi dengan serat benang, sedangkan kadar COD yang sangat tinggi disebabkan oleh adanya zat-zat organik yang terkandung didalamnya seperti zat pembasah, zat warna dan zatpembantu lainnya (Rahayu & Aulia, 2015).…”
unclassified
“…Sumber kitosan sangat melimpah di alam terutama dari hewan golongan krustase seperti udang dan kepiting (Pratiwi, 2014). Hasil penelitan (Rahayu & Aulia, 2015) menunjukkan bahwa peran kitosan ini mampu menurunkan TSS 88,79% dan warna 35,49% namun menurunkan kadar pH menjadi 4,98 yang disebabkan oleh penggunaan asam asetat sebagai pelarut kitosan.…”
unclassified